Beyond participation in community-based waste management: A study of co-production in Tanjungpinang, Indonesia - Mohd. Haiqal Haziq; Imam Yudhi Prastya; Dian Prima Safitri (Priviet Social Sciences Journal, 2026)
Waste management is a major challenge in delivering sustainable public services, particularly in archipelagic regions with limited infrastructure. The waste bank program was developed as an initiative to reduce waste generation while promoting community participation in waste management. However, existing studies on waste banks have primarily focused on policy implementation, community empowerment, and economic benefits, whereas research adopting a coproduction perspective remains relatively limited. This study aims to analyze the implementation of co-production in waste management through the waste bank program in Tanjungpinang City and identify the factors that facilitate and hinder its implementation. A qualitative approach with a case study design was used. Data were collected through observations, in-depth interviews, and document analysis involving the Tanjungpinang City Environmental Agency, Waste Bank managers, community members, and private sector representatives. The data were analyzed using NVivo 12 Plus through data reduction, display, and conclusion drawing. The findings indicate that the implementation of co-production involves multiple stakeholders; however, community participation has not yet been optimal across all stages of service delivery. The established collaboration has generated environmental, social, and economic benefits, including waste reduction, increased public awareness, and the creation of economic values. Nevertheless, the effectiveness of co-production remains constrained by limited community participation, inadequate facilities and infrastructure, weak coordination among stakeholders, and uneven dissemination of waste management education. This study highlights that the waste bank program represents a form of co-produced public service that fosters collaboration between the government and the community to achieve more effective and sustainable waste management.